Women's participation in childbearing decision-making and its effects on short-interval births in Rohingya refugee camps of BangladeshResearch in context - Md Nuruzzaman Khan; Shimlin Jahan Khanam (Elsevier, 2023)
Summary: Background: Women's involvement in family planning decision-making is significantly low among refugee women, potentially leading to an increased unintended and short interval pregnancies. This study aims to investigate the relationship between women's decision-making in childbearing and short-interval births among Rohingya refugee women in Bangladesh. Methods: Data from 719 women residing in three Rohingya refugee camps in Ukhiya, Cox's Bazar, Bangladesh, were analyzed. The outcome variable was birth spacing, categorized as short (<33 months between the two most recent births) or normal (≥33 months between the two most recent births). The primary explanatory variable was women's involvement in fertility decision-making with their partner, classified as never, sometimes, and always. Multivariate logistic regression analysis was conducted to assess the association between the outcome and explanatory variable while adjusting for potential covariates. Findings: 58% of births occurred within a short interval, while almost 48% of women reported no participation in fertility decision-making with their partner. Short interval birth was found to be increasing with decreasing women's participation in fertility decision-making with their partner. Women who sometimes or never made fertility decisions with their partner had 1.20 times (95% CI, 1.01-1.88) and 1.69 times (95% CI, 1.06-2.29) higher likelihood of short interval births, respectively, compared to women who always decided with their partner. Interpretation: Low women's participation in fertility decision-making with their partner among Rohingya refugees increases short interval births and adverse maternal and child health outcomes, including mortality. This highlights the need for counselling programs to educate and empower women, promoting joint fertility decision-making by couples. Funding: This research did not receive any specific funds.